Biotechnology Potential of Marine Fungi Degrading Plant and Algae Polymeric Substrates - Balabanova, Larissa; Slepchenko, Lubov; Son, Oksana; Tekutyeva, Liudmila (Frontiers in Microbiology, 2018)
Filamentous fungi possess the metabolic capacity to degrade environment organic matter, much of which is the plant and algae material enriched with the cell wall carbohydrates and polyphenol complexes that frequently can be assimilated by only marine fungi. As the most renewable energy feedstock on the Earth, the plant or algae polymeric substrates induce an expression of microbial extracellular enzymes that catalyze their cleaving up to the component sugars. However, the question of what the marine fungi contributes to the plant and algae material biotransformation processes has yet to be highlighted sufficiently. In this review, we summarized the potential of marine fungi alternatively to terrestrial fungi to produce the biotechnologically valuable extracellular enzymes in response to the plant and macroalgae polymeric substrates as sources of carbon for their bioconversion used for industries and bioremediation.